2007
DOI: 10.1590/s1676-06032007000200013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the decapod crustacean diversity in the Guayana Shield region aiming at conservation decisions

Abstract: Magalhães C. & Pereira, G. Assessment of the decapod crustacean diversity in the Guayana Shield region aiming at conservation decisions. Biota Neotrop. May/Aug 2007 vol. 7, no. 2. http://www.biotaneotropica.org. br/v7n2/pt/abstract?article+bn02007022007. ISSN 1676-0603.The current state of knowledge of freshwater decapod crustacean diversity of the Guayana Shield Region is briefly assessed, based upon information gathered from the scientific literature as well as unpublished data from academic theses, technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
3
17
0
1
Order By: Relevance
“…Magalhães and Pereira (2007) listed 10 pseudothelphusids and eight trichodactylids from the Negro River basin, while six and four, respectively, are herein reported from the Branco River basin. In total, the species richness of crab of the Xingu River basin is higher than that of the Branco River basin (13 vs. 10 species, respectively), but Branco River basin crab fauna is a little richer in pseudothelphusids than Xingu River basin fauna (six vs. five species, respectively).…”
Section: Genus Valdivia White 1847mentioning
confidence: 90%
See 2 more Smart Citations
“…Magalhães and Pereira (2007) listed 10 pseudothelphusids and eight trichodactylids from the Negro River basin, while six and four, respectively, are herein reported from the Branco River basin. In total, the species richness of crab of the Xingu River basin is higher than that of the Branco River basin (13 vs. 10 species, respectively), but Branco River basin crab fauna is a little richer in pseudothelphusids than Xingu River basin fauna (six vs. five species, respectively).…”
Section: Genus Valdivia White 1847mentioning
confidence: 90%
“…5-7). Magalhães and Pereira (2007) listed eight species as occurring in the Negro River, of which the Branco River is the main tributary, and four of them (M. laevifrons, P. dentata, S. pictus, V. serrata) are also recorded from Roraima henceforth. It would not be unexpected that at least some of the others could also be found in the lower Branco River if more intensive surveys of the area were carried out.…”
Section: Genus Valdivia White 1847mentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, Palaemon carteri (Gordon, 1935) was considered to be distributed in the Negro River basin (Magalhães and Pereira 2007). However, in a study on the morphological and molecular differentiation of two species of Palaemon from the Amazon basin, Carvalho et al (2014) concluded that the populations distributed in the Negro River basin were distinct and described a new species, Palaemon yuna, from this basin.…”
Section: Genus Palaemon Weber 1795mentioning
confidence: 99%
“…Surveys of decapod fauna using the Aquatic Rapid Assessment Program (AquaRAP) protocol in some South American rivers resulted in four species of crabs (one Pseudothelphusidae and three Trichodactylidae) from the upper and middle Rio Caura, Venezuela (Magalhães & Pereira, 2003), five species (three Pseudothelphusidae, two Trichodactylidae) from the upper Rio Essequibo, Guiana (Lasso et al, 2008), five species (two Pseudothelphusidae, three Trichodactylidae) from the upper Rio Cuyuní, Venezuela , four species (one Pseudothelphusidae, three Trichodactylidae) from Rio Pastaza, Ecuador and Peru (Magalhães, 2005), four species (two Pseudothelphusidae, two Trichodactylidae) from upper Rio Paragua, Venezuela (Mora-Day & Blanco-Belmonte, 2008), 12 presumptive species (eight Pseudothelphusidae, four Trichodactylidae) from river drainages of the Tumucumaque Moutains National Park, Brazil (Vieira, 2008), three species (one Pseudothelphusidae, two Trichodactylidae) from the confluence of the Rio Orinoco and Rio Ventuari, Venezuela (Pereira & García, 2006), and three species (one Pseudothelphusidae, two Trichodactylidae) from the middle Coppename River, Suriname (Pereira & Berrestein, 2006). According to Magalhães & Pereira (2007), the Guayana Shield region, including parts of Colombia, Venezuela, Brazil, Guyana, Suriname and French Guiana, harbors representatives of 33 species of freshwater crabs: 21 species of Pseudothelphusidae and 12 species of Trichodactylidae. Similarly, Pereira et al (2009) compiled the list of the decapod species from the Rio Orinoco basin, which drains large areas of the Guayana Shield and the Venezuelan Llanos in northern South America, and reported 16 species of pseudothelphusid and five species of trichodactylid crabs for the whole region.…”
Section: Species Diversitymentioning
confidence: 99%